Avaliação econômica e ambiental da adoção de práticas de produção mais limpa na indústria de fundição: estudo de múltiplos casos - Montel, Carlos Renato (2019)
Cleaner Production is an important approach to be applied in small foundries, as it offers viable alternatives for improvements in their production processes, allowing economic and environmental gains. It presents itself as an important tool for the prevention of environmental risks and impacts, while at the same time increasing the efficiency of processes, making all actions less aggressive to man and the environment. Unfortunately small foundries make little use of this practice, which would help in improving the products and services, using as an environmental alternative, the end-of-pipe treatment. Even the Brazilian legislation characterizing the generator as responsible for the destination of its waste, the scarcity of information and the lack of knowledge about the alternatives for this purpose, means that little attention is given by companies to such responsibility. This may be a result of deficiencies in inspection or the belief that actions aimed at preserving the environment carry high costs. This study aims to perform economic and environmental evaluation in the adoption of Cleaner Production practices and presents the results of the work carried out with four small foundries measuring gains in the foundry sector. Specifically, a bibliographic and bibliometric study was carried out on the subject, identifying the practices used and their consequences. The technique used for data collection was interview and observation, making it possible to compose a study of multiple cases. The methodology for environmental and economic evaluation of the implementation of eco-efficiency tools was applied in the four foundries to measure environmental and economic gain. It was found that Cleaner Production Practices bring benefits both in economic and environmental issues. However, the practices adopted by purely environmental aspirations are rare.